1989
DOI: 10.1017/s1049023x00029939
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Reanimatology Potentials: A Structured Interview Study in Armenia I. Methodology and Preliminary Results

Abstract: In general, preparations for disasters which result in mass casualties do not incorporate a modern resuscitation approach. We explored the life-saving potential of, and time limits for life-supporting first aid (LSFA), advanced trauma life support (ATLS), resuscitative surgery, and prolonged life support (PLS: intensive care) following the earthquake in Armenia on 7 December 1988. We used a structured, retrospective interview method applied previously to evaluation of emergency medical services (EMS) in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…The medical report with the longest reported time to rescue was Klain et al reporting on the 1988 Armenian earthquake with one victim saved "13-19 days" after the event (this was based on secondhand data from Soviet authorities and the authors are not more specific). 6 The next longest reported time to rescue was 8.7 days (209 h) as reported by Lopez in a 1989 follow-up evaluation of specific victims from the 1985 Mexico City earthquake. 7 The third longest time-to-rescue reported in the medical literature is 5.6 days (135 h) from the 1999 earthquake in Marmara, Turkey as reported by both Sever and Pocan.…”
Section: Medical Literature Reviewmentioning
confidence: 90%
“…The medical report with the longest reported time to rescue was Klain et al reporting on the 1988 Armenian earthquake with one victim saved "13-19 days" after the event (this was based on secondhand data from Soviet authorities and the authors are not more specific). 6 The next longest reported time to rescue was 8.7 days (209 h) as reported by Lopez in a 1989 follow-up evaluation of specific victims from the 1985 Mexico City earthquake. 7 The third longest time-to-rescue reported in the medical literature is 5.6 days (135 h) from the 1999 earthquake in Marmara, Turkey as reported by both Sever and Pocan.…”
Section: Medical Literature Reviewmentioning
confidence: 90%
“…The research identified 34 major earthquakes occurring during the period 1985-2003. In the published English-language medical literature during the study interval, the longest reported time to rescue was an imprecise 13 to 19 days after the 1988 Armenian earthquake in the Soviet Union 14. The next longest documented rescue was 8.7 days after the 1985 Mexico City earthquake,15 and 5.6 days after the 1999 Marmara earthquake in Turkey 16.…”
Section: Historical Evidence and The 2010 Haiti Earthquake Experiencementioning
confidence: 98%
“…DC studied the medical response to the earthquake in Armenia on 7 December 1988 as part of an on-site collaboration between the International Resuscitation Research Center of the University of Pittsburgh, USA, and the Institute of Reanimatology of the USSR Academy of Medical Sciences in Moscow, Russia [1]. …”
Section: Resultsmentioning
confidence: 99%
“…Comparing the 1988 earthquake in Armenia, the former republic of the Soviet Union (USSR) [1], with the attack in New York on 11 September 2001 reveals similarities in the potential resuscitation of victims. The Armenian earthquake, which was close to its capital Yerevan (see Fig.…”
Section: Introductionmentioning
confidence: 99%